A Particle Swarm Optimization based Fuzzy Logic Control for Photovoltaic System - Priyadarshi, Neeraj; Azam, Farooque; Sharma, Ashis; Kumar Bhoi, Akash; Kumar, Manish (International Journal of Engineering and Technology, 2018)
A Particle swarm optimizer (PSO)-Fuzzy logic based MPPT is used for optimal control in renewable energy system. It uses buck-boost converter, which acts as a maximum power point tracking. The proposed inverter comprises of mainly three functions viz. MPPT, DC-side voltage regulation and output grid-connected current, over changing insolation level. The system is connected to the grid to supply ac power which is accomplished by globally locating the maximum power point of the array. PSO algorithm is used to optimize thefuzzy values accurately. The PV practical implementation is linked with theSimulink based PSO-FLC method.Â Â